Osseointegrated implant as an auxiliary of orthodontic leveling in case of asymmetric vertical skeletal discrepancy – case report (Revista da Faculdade de Odontologia - UPF, 2019)
The aim of this work is to present a case report where an osteointegrated implant was used as skeletal anchorage unit in association with fixed orthodontic appliance in the treatment of an adult patient with vertical asymmetrical skeletal discrepancy. In this case report, the pre-existing osseointegrated implant in the region of element 21 was used as an aid of skeletal anchorage for the leveling of the upper occlusal plane by means of the straight-wire technique, Capelozza standard I slot .022 ", using the sequence of arches of nickel-titanium thermo-activated .014 ", .016", .017 "X.025" and .019X.025 ", followed by the steel arch .019" X.025". The results presented in this report demonstrated the osteointegrated implant as a good option, when used as anchorage resource to help orthodontics, providing better conditions of comfort and esthetics, as well as simplifying the technique.